Hungry brains: A meta-analytical review of brain activation imaging studies on food perception and appetite in obese individuals - Devoto, F.; Zapparoli, L.; Bonandrini, R.; Berlingeri, M.; Ferrulli, A.; Luzi, L.; Banfi, G.; Paulesu, E. (Neuroscience and biobehavioral reviews, 2018)
•We provide the first quantitative assessment of neurocognitive theories of obesity.•These results were obtained with quantitative meta-analyses of fMRI studies.•Overall, we provide support for an incentive sensitization theory of obesity.•Obese individuals have greater activation of reward regions for visual food cues.•The brain of obese individuals is more sensitive to hunger and less to satiety. The dysregulation of food intake in chronic obesity has been explained by different theories. To assess their explanatory power, we meta-analyzed 22 brain-activation imaging studies. We found that obese individuals exhibit hyper-responsivity of the brain regions involved in taste and reward for food-related stimuli. Consistent with a Reward Surfeit Hypothesis, obese individuals exhibit a ventral striatum hyper-responsivity in response to pure tastes, particularly when fasting. Furthermore, we found that obese subjects display more frequent ventral striatal activation for visual food cues when satiated: this continued processing within the reward system, together with the aforementioned evidence, is compatible with the Incentive Sensitization Theory. On the other hand, we did not find univocal evidence in favor of a Reward Deficit Hypothesis nor for a systematic deficit of inhibitory cognitive control. We conclude that the available brain activation data on the dysregulated food intake and food-related behavior in chronic obesity can be best framed within an Incentive Sensitization Theory. Implications of these findings for a brain-based therapy of obesity are briefly discussed.